PERAN PENDIDIKAN DASAR ISLAM DALAM MENCEGAH RADIKALISME - Noven Kusainun (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2020)
One of the features that shows that Islam is rahmatan lil'alamin is that Islam really values differences. The problem as well as the threat faced by Indonesia in the context of diversity is the emergence of radicalism. Not a little that the target of the radicalism movement is students at the elementary education level. The influence exerted for example through content on social media, radical religious movements, and provoking students to participate in spreading the understanding of radicalism. Students who are at the level of basic education are individuals in their growth and development who are easily influenced by the environment. The purpose of this study is to elaborate on the role of Islamic basic education in preventing radicalism. This research uses a qualitative approach with library research methods. The results in this study indicate that the role of Islamic basic education in preventing radicalism is to implement multicultural education. Multicultural education can be understood as a concept and context in the administration of education. The aim is that every learning that is carried out in a multicultural madrasa, both in religious learning, religious activities, and in other learning.